The influence of physical fitness degree and understanding of the concept of fitness on the quality of physical education sports and health learning - Jonas Solissa; Yellia Tomasoa; Mariana Ditboya Hukubun; Vicktor H R Apitulley; Tedi Purbangkara (Jurnal Pendidikan Jasmani Indonesia, 2026)
Penelitian ini bertujuan untuk menganalisis pengaruh derajat kebugaran jasmani dan pemahaman konsep kebugaran jasmani terhadap mutu pembelajaran pendidikan jasmani, olahraga, dan kesehatan (PJOK). Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei dan desain korelasional. Penelitian resimental pendidikan jasmani ini menggunakan desain korelasi ganda. Derajat kebugaran jasmani diukur menggunakan tes lari 12 menit (Cooper Test), pemahaman konsep kebugaran jasmani diukur melalui angket, dan mutu pembelajaran PJOK diukur melalui angket siswa. Sampel dalam penelitian ini adalah guru pendidikan jasmani di sekolah menengah pertama dan 30 siswa yang diambil secara acak. Di Kota Ambon, 30 siswa diambil dengan teknik analisis data purposive sampling menggunakan analisis regresi berganda. Hasil penelitian menunjukkan bahwa derajat kebugaran jasmani berpengaruh signifikan terhadap mutu pembelajaran PJOK (F = 7,945; t = 2,819; p = 0,009; R² = 0,221). Sebaliknya, pemahaman konsep kebugaran jasmani tidak berpengaruh signifikan terhadap mutu pembelajaran PJOK (t = 0,535; p = 0,597). Kesimpulan penelitian ini menunjukkan bahwa kebugaran jasmani guru berperan penting dalam meningkatkan mutu pembelajaran PJOK, sedangkan pemahaman konsep kebugaran jasmani belum menunjukkan pengaruh yang signifikan.   Abstract:This study aims to analyze the influence of physical fitness level and understanding of physical fitness concepts on the quality of learning in physical education, sports, and health (PJOK). This study employs a quantitative approach, utilizing a survey method and correlational design. This physical education regimen study uses a multiple correlation design. The level of physical fitness was assessed using a 12-minute run test (Cooper Test). Understanding of physical fitness concepts was measured through a questionnaire, and the quality of PJOK learning was evaluated through a student questionnaire. The sample in this study consisted of a physical education teacher from a junior high school and 30 randomly selected students. In Ambon City, 30 students were selected using purposive sampling and data analysis techniques, including multiple regression analysis. The results showed that the level of physical fitness had a significant effect on the quality of PJOK learning (F = 7.945, t = 2.819, p = 0.009, R² = 0.221). In contrast, understanding of physical fitness concepts did not have a significant effect on the quality of PJOK learning (t = 0.535; p = 0.597). The conclusion of this study reveals that teachers' physical fitness plays a crucial role in enhancing the quality of PJOK learning, whereas understanding the concept of physical fitness has not shown a significant influence.